Knowledge based bioinformatics from analysis to interpretation - Alterovitz, Gil; Ramoni, Marco F. (John Wiley & Sons, 2010)
"In order to deal with issues that arise from the current increase of biological data in genomic and proteomic research and present it effectively to a wider audience, broader coverage of recent developments in the field of knowledge-based systems and their applications is required. Most current texts are either outdated or do not include all the aspects in knowledge and data-driven representation, integration, analysis, and interpretation. This collection aims to address this issue by providing comprehensive coverage of knowledge driven approaches to bioinformatics"--Provided by publisher.